2018
DOI: 10.1039/c7ob02614e
|View full text |Cite
|
Sign up to set email alerts
|

H-Transfer reactions of internal alkenes with tertiary amines as H-donors on carbon supported noble metals

Abstract: A hydride transfer reaction with tertiary amines was observed in the presence of noble metals on a carbon support. Hydride transfer had been documented previously in terms of activated allyl-type carbon-carbon double bonds containing carbonyl derivatives in the presence of triethyl amine (conjugate reduction). The proposed mechanism is a hydride transfer reaction in which the metal serves as the reaction partner of the hydrido-metal iminium adduct formation. The saturation of a non-activated internal double bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…H-Transfer reactions of internal alkenes with tertiary amines on carbon-supported noble metals such as palladium, platinum, and rhodium was studied in the condensed phase [98]. The highest overall catalytic activity was observed for Pd/C (Pd/10 mol %) in the presence of N,N-diisopropylethylamine, 1-ethylpyrrolidine, and 1-ethylpiperidine, while methyl oleate and trans-5-decene were used as starting materials (Scheme 26) [98]. Scheme 26.…”
Section: Hydrogen Transfer With Palladiummentioning
confidence: 99%
See 1 more Smart Citation
“…H-Transfer reactions of internal alkenes with tertiary amines on carbon-supported noble metals such as palladium, platinum, and rhodium was studied in the condensed phase [98]. The highest overall catalytic activity was observed for Pd/C (Pd/10 mol %) in the presence of N,N-diisopropylethylamine, 1-ethylpyrrolidine, and 1-ethylpiperidine, while methyl oleate and trans-5-decene were used as starting materials (Scheme 26) [98]. Scheme 26.…”
Section: Hydrogen Transfer With Palladiummentioning
confidence: 99%
“…Triethylamine and amines with longer alkyl chain (n-butyl, n-pentyl, n-hexyl) showed minor hydrogen donation abilities. The formation of 1-ethyl-pyrrole (from 1-ethylpyrrolidine) and pyridine (from 1-ethylpiperidine) was observed, which clearly indicated that the source of the newly incorporated two hydrogen atoms was the amine [98]. Two modes of activation of the alkene were described: one possibility if the alkene competitively adsorbs on the metal with the alkyl amine Scheme 26.…”
Section: Hydrogen Transfer With Palladiummentioning
confidence: 99%
“…In addition to the advantages in DODH, isopropanol is a good hydrogen donor for the CTH reaction. CTH reactions using isopropanol as a hydrogen donor have garnered much attention as an alternative to direct hydrogenation because the hydrogen donor is easy to handle and environmentally friendly, minimizing possible hazards. While CTH reactions have been mostly accomplished using noble-metal complexes, several effective heterogeneous catalysts for the CTH of ketone, imines, and polarized alkenes have been reported. …”
Section: Introductionmentioning
confidence: 99%
“…The crucial hydrogenation reaction has gained increasing interest, because it is widely utilized in span from industrial materials to activated drugs synthesis . In general, there are two strategies for the hydrogenation reaction; one is the direct hydrogenation with hydrogen gas, and the other one is the convenient and powerful transfer hydrogenation, referring to the addition of hydrogen to a molecule from a non‐H 2 hydrogen source.…”
Section: Applications Of Pd/cmentioning
confidence: 99%